FACTORS THAT AFFECT DIVIDEND POLICY DURING THE COVID-19 PANDEMIC - Aristie, Evelyn; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2025)
This research aims to obtain empirical evidence regarding the influence of free cash flow, business risk and investment opportunity set on dividend policy in banking companies listed on the Indonesia Stock Exchange in the 2020-2022 period. Sample selection was carried out using purposive sampling, resulting in a total sample of 13 companies. Next, data model selection, classical assumption testing, data analysis and hypothesis testing are carried out. The data was processed using the E-views 12 application and the research model used was random effect model (REM). The research results show that dividend policy, which is the dependent variable, is not influenced by free cash flow, business risks and investment opportunities. The absence of a significant influence from these three variables could be due to the ongoing Covid-19 pandemic during the research.